The effects of bovine bone scaffold on the microscopic biological response of human chondrocytes - Baharudin, Abdullah (Pusat Pengajian Sains Perubatan Universiti Sains Malaysia, 2008)
Introduction In the creation of cartilaginous tissue, the choice of suitable scaffold remains a great challenge. The current available scaffold either natural or synthetic still does not meet the requirement of a scaffold for cartilage tissue engineering. The ideal scaffold provides mechanical stability to the individual cell as a construct or transitional framework before synthesis of new extra cellular matrix. Objective The aim of this study was to produce bovine bone as a tissue engineering construct for cartilage reconstruction and to determine the effects of bovine bone on biological human chondrocyte in vitro. Method Human chondrocytes were cultured and seeded into bovine scaffold with seeding density of 1 x 105 cells per 1 00 ul I scaffold and incubated for 24 hours, 2 days, 5 days and 7 days. Proliferation and viability of the cells were measured by mitochondrial dehydrogenase activity (MTT assay), adhesion study was analyzed using Scanning Electron Microscopy (SEM) and differentiation study was analyzed by lmmunoflorescent staining using Confocal Laser Scanning Electron Microscopy (CLSM). Result The data showed the presence of proliferation and viability of the cells on the scaffolds by MTT method within 24 hours to 7 days observed. SEM pictures revealed presence of chondrocytes located on the scaffolds, showed increasing number of cell within the days and that cells readily grew on the surface and into the open pores of the scaffold. lmmunoflorescent staining detected collagen type II on the scaffolds which was increasing within the days. Conclusion The results showed the potential of bovine bone as three dimensional scaffold for cartilage tissue engineering because of the good cells proliferation, attachment, maturity, non toxic, safe, easily resourced and relatively cheap.